The Effect of Voluntary Disclosure on Investment Inefficiency - Guttman, Ilan; Meng, Xiaojing (The Accounting Review, 2021)
ABSTRACT We introduce real decisions (a project choice decision, an investment scale decision, and an information acquisition decision) to the Dye (1985) voluntary disclosure framework and examine how the prospect of voluntary disclosure affects managers' real decisions. Riskier projects lead to more volatile environment and hence entail higher efficiency loss at the subsequent investment scale decision stage if managers are uninformed. If managers are informed, they can withhold bad information, and the value of this option is higher for riskier projects. We show that the voluntary nature of managers' disclosure may lead to two types of inefficiencies: (1) managers may choose riskier projects, which generate lower expected cash flow due to the higher efficiency loss at the subsequent decision stage, and (2) managers may over-invest in information acquisition, because informed managers with bad information have the option to pool with uninformed managers and benefit from being overpriced.